The role of interpersonal relationship in Nora Seed's psychological journey in The Midnight Library - Salya Arwanda Chairunnisa; Sri Sumaryani (Universitas Negeri Semarang, 2025)
Infants' early experiences with their mother or caregiver shape how they build relationships in the future and internalize the emotional experience of objects. The quality of relationships formed with significant others can influence psychological growth. Matt Haig's The Midnight Library depicts how Nora Seed, the main character in the novel, relates to important people in her life that affect her psychological state. This study aims to identify and explore how interpersonal relationships can affect Nora Seed's psychological conditions in Matt Haig's The Midnight Library. This study employs a descriptive qualitative approach, drawing on Klein's object relations theory, because it enables researchers to explore and analyze narratives and dialogues in depth and holistically through careful data collection and detailed analysis. The results of this study show that Nora Seed's initial relationship with her parents as caregivers influences the formation of relationships with other significant people. She viewed her parents with ambivalence and as